Pediatric epidemiology of skin disorders in a mediterranean population with a nonreferral-based health-care system: A retrospective large series analysis - Boutros Soutou; Jason El Jalkh; Élio Ibrahim; Ramy Abou Jneid; Josiane Helou; Roland Tomb (Wolters Kluwer Medknow Publications, 2023)
Introduction: Data from the Levant regarding pediatric dermatoses are limited. The objective was to estimate the prevalence of pediatric dermatoses in a health-care system that allows every patient to directly reach a specialist. Patients and Methods: It is a single-center, chart review, epidemiological study of patients who consulted, between 2010 and 2022, at the general dermatology department of a tertiary care university hospital. A random draw of 10% of the files was screened. Patients aged between 0 and 18 years at the time of consultation were included and their files were analyzed. Results: The study population consisted of 151,050 files, of which 10% were manually screened. Finally, 2313 "pediatric" files were analyzed, corresponding to 15.3% of the sample, with a female-to-male ratio of 1281/1032 (1.24). Of these analyzed files, 2912 diagnoses were distributed in the age categories as follows: 464 (16%) at preschool age, 1134 (39%) at school age, and 1314 (45%) at adolescence. The most prevalent diagnoses in males were acne (19.6%), atopic dermatitis (9.7%), and molluscum contagiosum (8.1%); in females, acne (27.4%), atopic dermatitis (9.4%), and warts (5.8%). Acne was the most frequent diagnosis overall (24%) and in the adolescents' subgroup, with a female-to-male ratio of 1.77. The prevalence of atopic dermatitis decreased from 21.1% at preschool age to 10.9% at school age to 4.3% in adolescence. The most prevalent diagnoses at school age were molluscum contagiosum and warts. Conclusion: These updated percentages help configure suitable public health strategies for children in countries of approximate genetic background and similar life habits.